Screening of a novel bioflocculant-producing strain of Bacillus sp. and research for its flocculation characteristics - CAO Fang; YU Xiu-mei; GUO Juan-li; HE Min; PAN Kang-cheng (浙江大学学报. 农业与生命科学版, 2011)
A novel bioflocculant-producing Bacillus sp. was isolated from soil by streak plate method, and screened out by an index that the fermentation broth flocculated kaolin suspension. The strain was identified by physiological and biochemical characteristics and 16S rDNA sequence analysis. The effect of the factors such as fermentation broth dosage, Ca2+ concentration and pH on the flocculation were investigated. The results revealed that a novel bioflocculant-producing bacterium, named MBFF6, was isolated from soil and identified as Bacillus megaterium; its flocculating rate could achieve 95.7%; the optimal condition for flocculation was as follows: fermentation broth dosage of 2%, Ca2+ concentration of 4.5 mmol·L-1 and pH 7.0. The bioflocculant was produced during the bacterial growth and was an extracellular product which was distributed in the culture broth.